Interdisciplinary practices for prevention and control of arterial hypertension and diabetes mellitus in elderly (Research, Society and Development, 2020)
The objective of the study was to analyze the productions available, with emphasis on those that contributed most to the control and prevention of SAH and DM performed in primary care; and discuss, in the light of the reference, the outstanding actions for the control and prevention of the referred diseases. This is an integrative review of a qualitative approach carried out from August to September 2020, using the Virtual Health Library (VHL) databases. The selection of publications followed the guidelines of the PICo advanced search strategy, respecting the peculiarities and distinct characteristics of each database. The descriptors were combined with the Boolean connector AND and OR. The final sample of the study resulted in 35 articles, the majority of which (42%) was published between 2010 and 2014, about 63% are related to field research, 97% of publications had more than 3 authors and 83% were in the English language. The researchers' preference was evidenced by the quantitative approach for conducting the research (49%), the majority with unspecified research type (66%). As for the techniques used by the authors, 20% of the data were collected through a questionnaire, 17% through interviews and 54% by other techniques. It is concluded that care when performed in a multidisciplinary and interdisciplinary way produces benefits for the management of the chronic diseases in question, reaching the objectives of this study and showing the main benefits of the development of these practices in primary care.